PENDAMPINGAN SEPTEMBER HITAM: PEMBERDAYAAN KADER GERAKAN MAHASISWA NASIONAL INDONESIA (GMNI) JEMBER DAN MASYARAKAT UMUM DALAM UPAYA PENINGKATAN BERPIKIR KRITIS TERHADAP OTORITARIANISME DAN IMPUNITAS KEKERASAN MASYARAKAT SIPIL - Muhammad Agung Pramono Putro (Adiba Aisha Amira, 2026)
This community service activity was a response to the coercion of students and civil society groups in August-September 2025, known as Black September. Protests in various cities, including the GMNI demonstration in front of the Indonesian Parliament Building on September 1, 2025, faced excessive force from the authorities, mass arrests, and alleged human rights violations. The activity took the form of a panel discussion, which began with a screening of the documentary Dirty Vote (2024) by Dandhy Dwi Laksono, analyzed by three constitutional law experts, Zainal Arifin Mochtar, Bivitri Susanti, and Feri Amsari. The screening was followed by a presentation on the concept of authoritarianism and impunity for perpetrators of state violence against civilians. The participatory discussion involved cadres from GMNI Jember and 27 members of the general public, to reflect on the current repressive apparatus response. A Paulo Freire based conscientization approach was used to raise participants critical awareness in advocating for victims of civil violence and the criminalization of torture. The results of the activities showed an increase in understanding and commitment to advocacy, thus strengthening GMNI's role as an organization that does not want its presence in civil society circles.